2016
DOI: 10.1177/0363546516672651
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Socioeconomic Status on the Choice of Treatment for Patients With Cruciate Ligament Injuries in the Knee: A Population-Based Cohort Study

Abstract: All Swedish citizens are entitled by law to the same quality of health care; therefore, unmotivated differences in treatment between different socioeconomic groups are to be seen as a challenge. It is important to evaluate the specific mechanisms by which the patient's SES influences the decision of whether to treat a cruciate ligament injury operatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 99 publications
2
21
1
1
Order By: Relevance
“…Previous studies on primary ACLR reported that younger age, lower socioeconomic status, and public insurance are all associated with delays in care and additional surgeries at time of primary reconstruction. 9,10,30,31 In our study, insurance was evaluated as a potential risk factor for subsequent (revision or contralateral) ACLR. We found no difference in subsequent (revision or contralateral) ACLR risk between public and private insurance in the overall cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on primary ACLR reported that younger age, lower socioeconomic status, and public insurance are all associated with delays in care and additional surgeries at time of primary reconstruction. 9,10,30,31 In our study, insurance was evaluated as a potential risk factor for subsequent (revision or contralateral) ACLR. We found no difference in subsequent (revision or contralateral) ACLR risk between public and private insurance in the overall cohort.…”
Section: Discussionmentioning
confidence: 99%
“…13 In a Swedish study that examined the relationships between education level, household income, and likelihood of undergoing surgical treatment for cruciate ligament injury, the investigators found that patients with higher family income and/or education level were more likely to undergo surgical treatment. 16…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic factors have been shown to be associated with stoma reversal rate [ 15 , 17 , 18 ]. Income, education and occupation are well-known variables used for classification of socioeconomic status [ 19 , 20 ]. Kuryba et al [ 15 ] evaluated factors affecting stoma reversal rate in 4879 rectal cancer patients.…”
Section: Introductionmentioning
confidence: 99%